Influência da Resposta inflamatória na Resposta virológica sustentada em pacientes com Hepatite C Crônica genótipo 1 durante o tratamento antiviral com terapia tripla - Winckler, Fernanda Cristina [UNESP] (2016)
Hepatitis C is an infectious disease which becomes chronic in about 85% of infected people who can develop cirrhosis and hepatocellular carcinoma. Antiviral therapy isn’t effective in many patients, especially when these patients are genotype 1 and have advanced fibrosis, the inflammatory response also plays a role on sustained virological response (SVR) during treatment with Pegylated (PegIFN) plus Ribavirin (RBV). The aim of this study was evaluate the influence of the inflammatory response by cells and cytocines/chemokines on the virologic response of the patients under antiviral treatment with triple therapy. We included patients with HCV RNA+, naive, genotype 1, both male and female and with advanced fibrosis F3 (n=6); F4 (n=21) for triple treatment regimen. Patients had their samples collected and analyzed at weeks 0 and 12 of treatment and the following parameters were analyzed: IL- 2, IL-4, IL-6, IL-8, IL-10, IL-17A, TNF-α, IFN-γ RANTES, MCP-1, MIG, IP-10 by flow cytometry (CBA method). Control group of 15 healthy volunteers and 27 patients, who were separated into GI (SVR) and G2 (not SRV), were included, the SVR rate was 63%. Patients with chronic hepatitis C had higher circulating levels of IP10, MCP-1, MIG, RANTES, IL-8 and IL-6 compared with healthy volunteers, when G1xG2 were compared, levels of RANTES (p=0,040 and IL-6 (n=0,02) were associated with a SVR at week 0 and its levels were lower in G1; at week 12, levels of RANTES (p=0,04) and IL-8 (p=0,01) were associated with a SVR and its levels were higher in G2. The comparison between weeks 0 and 12 showed that, in G1, the IL6 levels (p = 0.02) and MCP-1 (p = 0.001) were associated with the treatment and in G2, the parameters associated with the treatment were RANTES (p = 0.05) and MCP-1 (p = 0.01). The results suggest that the cytocine IL-6 and chemokine RANTES are associated with SVR at week 0. At week 12, RANTES as well as IL-8 influence in SVR during antiviral therapy in triple regimen. When weeks 0 and 12 in patients SVR are compared, the cytocine IL-6 is associated with treatment. In non-SVR patients, RANTES is associated with treatment and MCP-1 is associated with independent treatment of the patient's response.